Tanzania: Impacts of the Ukraine and Global Crisis on Food Systems and Poverty - Diao, Xinshen; Dorosh, Paul; Ellis, Mia; Pauw, Karl; Thurlow, James (2022)
Presentation prepared by Xinshen Diao, Paul Dorosh, Mia Ellis, Pauw Karl, James Thurlow, all with the International Food Policy Research Institute, Washington DC. This is part of the Global Crisis Country Series.